(untitled) (International journal of artificial intelligence, 2025)
The article explaines the importance of bringing up the modern young generation on the basis of spiritual education and a new worldview, to further strengthen the feelings of patriotism, love and loyalty to the motherland among not only young people, but also all members of our society at the current stage of development. The importance of national spirituality and ideology in the acquisition of modern knowledge and the expansion of the worldview of young people is analyzed as well.